2011
DOI: 10.1029/2011wr010498
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long‐term irrigation with treated wastewater on the hydraulic properties of a clayey soil

Abstract: [1] The increasing demand for freshwater (FW) for domestic use turns treated wastewater (WW) into an attractive source of water for irrigated agriculture. The main goal of this study was to evaluate the impact of 15 yrs of irrigation with WW on hydraulic properties and flow processes in a clayey soil, compared to FW use. It also quantitatively addressed the distribution with depth along the soil profile of that impact on soil hydraulic properties. Standard methods used in soil physics at the laboratory scale, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
1
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 54 publications
6
70
1
5
Order By: Relevance
“…To the knowledge of the authors, this study is the first to compare the unsaturated HC of clayey soils irrigated with FW and TWW on adjacent test sites in-situ. Assouline and Narkis (2011) applied the MDI in a column study with disturbed clayey soil samples from a TWW-and FW-irrigated test site and showed lower infiltration rates for the TWW-irrigated samples. Vogeler (2009), using disc permeameters, calculated the HC of wastewater and TWW disposal sites and adjacent non-irrigated areas on sandy loam (site Taupo, T) and loamy sand (site Levin, L).…”
Section: Discussionmentioning
confidence: 99%
“…To the knowledge of the authors, this study is the first to compare the unsaturated HC of clayey soils irrigated with FW and TWW on adjacent test sites in-situ. Assouline and Narkis (2011) applied the MDI in a column study with disturbed clayey soil samples from a TWW-and FW-irrigated test site and showed lower infiltration rates for the TWW-irrigated samples. Vogeler (2009), using disc permeameters, calculated the HC of wastewater and TWW disposal sites and adjacent non-irrigated areas on sandy loam (site Taupo, T) and loamy sand (site Levin, L).…”
Section: Discussionmentioning
confidence: 99%
“…The primary risks associated with TE irrigation involve high concentrations of salts, especially sodium, and of organic compounds (Feigin et al, 1991; Balks et al, 1998; Hamilton et al, 2007; Pedrero et al, 2010). Recent studies have shown that long‐term effects of TE irrigation resulted in a significant degradation of soil structure and hydraulic properties due to increased exchangeable sodium percentage (Leij et al, 2004; Lado et al, 2005; Assouline and Narkis, 2011, 2013; Levy et al, 2011). Evidence from other studies have shown other negative effects related to chemical aspects (Xiong et al, 2001; Wallach et al, 2005; Lado et al, 2012), as well as human health and other ecological risks associated with introduction of pathogenic microorganisms, heavy metals, and toxic organic compounds into the soil and crop (Toze, 2006; Pedrero et al, 2010; Scheierling et al, 2010; del Mar Alguacil et al, 2012).…”
Section: Modeling Soil Supporting and Degrading Processesmentioning
confidence: 99%
“…High clay content in the soil could lead to soil swelling during wetting and thus induce dynamic changes in soil porosity and hydraulic properties and consequently affect infiltration [Raats and Klute, 1969;Philip, 1970;Smiles, 1974;Sposito, 1975;Giraldez and Sposito, 1985]. Soil sodicity and electrolyte concentration of the wetting fluid could also have a significant impact on soil hydraulic properties and on the infiltration process [Quirk and Schofield, 1955;McNeal and Coleman, 1966;Bresler et al, 1982;Jury et al, 1991;Russo, 2005;Assouline and Narkis, 2011]. Temporal variability of intensity within the same rainfall event could induce drainage and redistribution to occur simultaneously in the same soil profile.…”
Section: Infiltration Under Special Conditionsmentioning
confidence: 99%